2021
DOI: 10.1111/1759-7714.13933
|View full text |Cite
|
Sign up to set email alerts
|

GPR12 inhibits migration and promotes apoptosis in esophageal cancer and hypopharyngeal cancer cells

Abstract: Background G protein‐coupled receptor 12 (GPR12) is an orphan receptor with no confirmed endogenous ligands. It plays important roles in both physiological and pathological conditions such as neurogenesis and neural inflammation. However, it remains unclear whether GPR12 regulates carcinogenesis and progression in head and neck squamous cell carcinoma (HNSCC), such as esophageal cancer (EC) and hypopharyngeal cancer (HC). Methods The Cancer Genome Atlas (TCGA) database was applied to explore the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…4 A). Based on the literatures included in PubMed, GPR12, ITM2B, ZNF24, and NSL1 were selected as the candidate targets due to the low expressions in various cancers [ 17 20 ]. We examined the mRNA expressions of these four genes in T24 cells, and GPR12 showed the most significant downregulation after miR-105-5p mimic transfection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 A). Based on the literatures included in PubMed, GPR12, ITM2B, ZNF24, and NSL1 were selected as the candidate targets due to the low expressions in various cancers [ 17 20 ]. We examined the mRNA expressions of these four genes in T24 cells, and GPR12 showed the most significant downregulation after miR-105-5p mimic transfection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed that GPR12 induces apoptosis by activating caspase-7, and inhibits the migration of hypopharyngeal, laryngeal, and esophageal cancer cells by promoting the expression of EMT-related proteins in hypopharyngeal, laryngeal, and esophageal cancer cells (46). The work of Hala El-Zimaity et al showed that Helicobacter pylori is associated with esophageal cancer, leading to increased gastric acid secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic cancer cells (PANC-1) cells, Park et al observed that overexpression of GPR12 induced K8 phosphorylation and perinuclear reorganization, promoting migration and invasion by changing the viscoelasticity (13). However, Zhang et al demonstrated that GPR12 as a potential tumor suppressor-mediated cell migration and apoptosis in esophageal cancer and hypopharyngeal cancer (21), indicating that the characteristics of GPR12 varied in different types of cancer. Here, we found that GPR12 mRNA expression is extremely low in the majority of cancer types and significantly decreased in glioblastoma multiforme (GBM), brain lower grade glioma (LGG), and skin cutaneous melanoma (SKCM) tissues than matched normal tissues through pan-cancer analysis of GEPIA (Supplementary Figure 2A).…”
Section: Discussionmentioning
confidence: 99%